DAMPAK MEDIA, PENENTUAN AGENDA (AGENDA SETTING), DAN TEORI THE SPIRAL OF SILENCE - Sumaina Duku (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2014)
The impact of media, Determination Agenda (Agenda Setting) and Theory of The Spiral Of Silence is a three-part study of the theory of Mass Communication. Theories about the impact of the mass media is divided into four stages: All-powerful media, Theory of powerful media put to the test, Powerful media rediscovered, and Negotiated media influence. Determination of the Agenda (Agenda Setting) is a process of media influence either expected or unexpected in which the relative importance of the events reported, or character issues that affect memory in the minds of the public and the relative importance in news reporting. Assuming that the media attention in revealing a topic that is associated with the news audience. Indirect influence of the media on opinion but only on what is thought by societies. The Spiral Of Silence Theory states that individuals have the sense organs similar to the statistics used to determine the opinions and modes of behavior which are approved or not approved by their environment, as well as